ADOLESCENT MOTHERHOOD AND CAPITAL: INTERACTION EFFECTS OF RACE/ETHNICITY ON HARSH PARENTING. Issue 1 (13th December 2012) - Lee, Yookyong
<x xml:space="preserve">Abstract</x> This study used large, longitudinal data to examine the moderating effects of race and ethnicity of mothers on the associations between (a) adolescent motherhood, (b) human, social, and cultural capital factors, and (c) harsh parenting. The study sample included adolescent mothers who were 19 years old or younger (n = 379) and adult mothers 26 years old or older (n = 881). Of these, about 31% were White, 48% Black, and 21% Hispanic. The Parent to Child version of the Conflict Tactics Scales was used as a proxy for maternal harsh parenting when their children were 3 years old. Results indicated that adolescent motherhood and different capital factors contributed to the prediction of maternal harsh parenting for each racial/ethnic group. The findings suggest the importance of differentiating strategies for preventing adolescent motherhood and for reducing the likelihood of harsh parenting among different racial/ethnic groups of mothers.